Doomscrolling di Era Digital Berdasarkan Dikotomi Kendali Stoikisme untuk Kesejahteraan Psikologis - Nissa Aurellia Putri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The rapid acceleration of digital information has intensified the phenomenon of doomscrolling the compulsive consumption of negative news that erodes psychological stability and self-control. This study analyzes doomscrolling behavior through the Stoic Dichotomy of Control, which distinguishes between what is within human agency and what is not. Using a qualitative descriptive-analytic design supported by thematic content analysis, it synthesizes insights from empirical psychology, digital sociology, and classical Stoic philosophy. The findings demonstrate that persistent exposure to distressing online content correlates with anxiety, cognitive exhaustion, and reduced emotional agency, with global surveys indicating that approximately 82% of adolescents engage in habitual doomscrolling. The Stoic concept of prohairesis rational moral choice—emerges as a vital strategy for managing digital impulses by focusing on internal judgment rather than uncontrollable external stimuli. The research concludes that applying Stoic ethical principles within digital literacy and mental health education can enhance self-regulation, mitigate compulsive media behavior, and promote psychological resilience amid the incessant flow of online information